Pengaruh Religiulitas Dan Peer Support Terhadap Perilaku Pacaran Siswa MTs - Ariel Gymnastiar Inzaghi; Alaiya Choiril Mufidah (SINDA: Comprehensive Journal of Islamic Social Studies, 2026)
This study aims to determine the influence of religiosity and peer support ondatingbehavior among MTs students in Blitar. The method used in this study is quantitativeand analyzed using multiple linearregression analysis. The participants of this study were 150 students in Blitar with an age category of 11-17 years. The results of the study show that partially there is no significant influence between religiosity on dating behavior with a significance value of 0.569, but there is a positive and significant influence between peer support on dating behavior with a significance value of 0.035. Simultaneously, both variables influence students' dating behavior, which is supported by the F test value of 3.126 (p >0.05) and the R Square value of 4.1%, which means that dating behavior is influenced by religiosity and peer support,while the remaining 95.9% is influenced by other factors outside this study. This study is important to examine in order to bridge the theoretical gap and offer new perspectives on the determinants of dating behavior among madrasah students, particularly at the MTs level. In general, the dynamics of dating among adolescents are influenced by both internal and external stimuli.